Cytotoxicity of Dental Cements on Soft Tissue Associated with Dental Implants - Prashant Bajantri; Shobha J. Rodrigues; K. Shama Prasada; Umesh Y. Pai; Thilak Shetty; Sharon Saldanha; M. Mahesh; Puneeth Hegde; Ann Sales; Sandipan Mukherjee; Vignesh Kamath (Hindawi Limited, 2022)
Purpose. To investigate and compare the cellular host response of human gingival fibroblasts (HGF) on four currently used cements. Methods and Material. 5 cement pellet samples were made for each of the 4 test cements (n = 20). The cements used for this study were zinc phosphate, zinc oxide noneugenol (ZOE), RelyX U200, and glass ionomer cement (GIC). One commercially available cell line was used to investigate the cytotoxicity of peri-implant tissues. Direct contact cell culture testing was conducted following International Organization for Standardization (ISO) methods 10993-5 and 10993-12 (MTT assay test). Cell cultures without dental cement were considered as control. Cells were allowed to grow and confluence over 48 hours after subcultivation according to standard laboratory procedures. The cells were kept in direct contact with the cement samples for 24 hours before being subjected to analysis. All specimens were tested in triplicate to validate the results. Quantitative evaluation of cytotoxicity was done to measure cell death and inhibition of cell growth. Results were analyzed using 1-way ANOVA (a = 0.05) followed by Tukey B post hoc test. Results. The results of the study showed that HGF was vulnerable to the dental cement test material. GIC, zinc phosphate, ZOE, and resin cement were cytotoxic in decreasing order, respectively, and significantly reduced the cell viability after exposure to HGF p<0.001. Conclusions. Within the limitations of this in vitro cellular study, results indicated that the test dental cements were cytotoxic to HGF. The highest cytotoxicity was observed in GIC followed by zinc phosphate, ZOE, and resin cement.